Dynamics of Emigration: Bangladesh Case (Journal of the Asiatic Society of Bangladesh, Humanities, 2023)
Overseas migration has attracted a lot of attention from policymakers and academics in Bangladesh. The writings and debates on migration in Bangladesh have centred around the economic benefits of migration as well as its social implications. This paper is a contribution to this literature. The detailed analysis of emigration patterns using the data provided by the BMET, but not aggregated and complied before, adds to the ongoing debates on overseas migration in Bangladesh. Disaggregate analysis is provided in this paper, from the 2004 till date, on the overseas migration of men and women over the years, along with their occupation, age, and skill profile. In addition, this paper brings a regional dimension into the discussion of the migration literature in Bangladesh. The sharp variation in the intensity of overseas migrations across the different districts of Bangladesh gives us new insights for policy that links overseas migration as a panacea for some of the development challenges that the country faces. The reach of overseas migration to give gains to households that are in highly underdeveloped regions remains limited and, in some ways, continues to keep them trapped in a vicious circle of underdevelopment.Journal of the Asiatic Society of Bangladesh (Hum.), Vol. 68(1), 2023, pp. 69-97